2014
DOI: 10.1086/677632
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the Transmission of Multidrug-Resistant Organisms: Modeling the Relative Importance of Hand Hygiene and Environmental Cleaning Interventions

Abstract: OBJECTIVES Hand hygiene and environmental cleaning are essential infection prevention strategies, but the relative impact of each is unknown. This information is important in assessing resource allocation. METHODS We developed an agent-based model of patient-to-patient transmission—via the hands of transiently colonized healthcare workers (HCW) and incompletely terminally cleaned rooms—in a 20-patient intensive care unit. Nurses and physicians were modeled and had distinct hand-hygiene compliance levels on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 18 publications
0
66
0
4
Order By: Relevance
“…Transmission risk is magnified in the ICU compared with other healthcare settings because an average ICU patient has been estimated to receive 178 interactions with providers daily (11). Despite data showing greater efficacy reducing transmission with improvements in hand hygiene as compared with other prevention measures (12), hand hygiene rates in the ICU are reprehensibly poor, with a median compliance between 30% to 40% (13). Scrupulous adherence to hand hygiene is critical as every interaction is a potential source of transmission.…”
Section: Infection Preventionmentioning
confidence: 99%
“…Transmission risk is magnified in the ICU compared with other healthcare settings because an average ICU patient has been estimated to receive 178 interactions with providers daily (11). Despite data showing greater efficacy reducing transmission with improvements in hand hygiene as compared with other prevention measures (12), hand hygiene rates in the ICU are reprehensibly poor, with a median compliance between 30% to 40% (13). Scrupulous adherence to hand hygiene is critical as every interaction is a potential source of transmission.…”
Section: Infection Preventionmentioning
confidence: 99%
“…2 The healthcare environment as well is a target for technology that reduces bioburden (eg, disinfection with ultraviolet-C light) and thus reduces risk of transmission. [3][4][5] Additionally, the literature describing CP's negative impact on patient care has continued to proliferate. Studies have suggested that CP may increase patient adverse events such as falls and pressure ulcers, 6,7 isolation, and depression, 8 perhaps because healthcare workers do not spend as much time in direct patient care with patients in CP.…”
mentioning
confidence: 99%
“…6 We modified an existing agent-based model of MDRO transmission developed using NetLogo version 5.0.5 software 7 that was used in a previous study. 8 (A description of the model pseudocode is provided as an online supplement.) We modeled the intensive care unit (ICU), where MDROs are prevalent and antibiotic usage is high.…”
Section: Methodsmentioning
confidence: 99%